1994
DOI: 10.1002/sdr.4260100214
|View full text |Cite
|
Sign up to set email alerts
|

Learning in and about complex systems

Abstract: Change is accelerating, and the complexity of the systems in which we live is growing.Increasingly change is the result of humanity itself. As complexity grows so do the unanticipated side effects of human action, further increasing complexity in a vicious cycle.Many scholars call for the development of 'systems thinking' to improve our ability to manage wisely. But how do people learn in and about complex dynamic systems? Learning is a feedback process in which our decisions alter the real world, we receive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
238
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 911 publications
(270 citation statements)
references
References 59 publications
2
238
0
3
Order By: Relevance
“…Several studies such as [5] [9]- [12] have confirmed that contingency is not managed or reported by project and cost managers. This is due to the challenges associated with the [12] and [13] submitted that the problem of incorporating project complexity into actual management is affecting the construction contingency management.…”
Section: Challenges Associated With the Management Of Contingency Funmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies such as [5] [9]- [12] have confirmed that contingency is not managed or reported by project and cost managers. This is due to the challenges associated with the [12] and [13] submitted that the problem of incorporating project complexity into actual management is affecting the construction contingency management.…”
Section: Challenges Associated With the Management Of Contingency Funmentioning
confidence: 99%
“…This is due to the challenges associated with the [12] and [13] submitted that the problem of incorporating project complexity into actual management is affecting the construction contingency management. [2] also confirmed that project complexity and inherent uncertainty of the financial performance of constructed facilities, development funding, control of cost and schedules make exact budget needs impossible to forecast accurately.…”
Section: Challenges Associated With the Management Of Contingency Funmentioning
confidence: 99%
“…Cognition and learning of complex systems "Complex systems are commonly found in natural and physical sciences" (Hmelo et al, 2000, p. 247), and there is an increasing interest in researching cognition and learning about natural complex systems, such as the respiratory system, Earth system and ecosystems, in the last twenty years (e.g., Salner, 1986;Sterman, 1997;Goldstone & Sakamoto, 2003;Hmelo et al, 2000Hmelo et al, , 2004Hmelo et al, , 2008Ben-Zvi-Assaraf et al, 2005;Magntorn et al, 2007;Booth-Sweeney & Sterman, 2007).…”
Section: Environmental Educationmentioning
confidence: 99%
“…Research on environmental education focusing on ecological knowledge held by local users is limited to a few examples (i.e., Reid et al, 2002Reid et al, , 2004, as is research in the cognitive and learning sciences regarding people's understanding of natural complex systems (e.g., Salner, 1986;Sterman, 1997;Goldstone & Sakamoto, 2003;Ben-Zvi-Assaraf et al, 2005;Magntorn et al, 2007;Booth-Sweeney & Sterman, 2007), and in particular on ecosystems' complexity (e.g., Hmelo et al, 2000;Hmelo-Silver et al, 2004;Hmelo-Silver et al, 2008). Research on workplace learning and the human-nature relationship concerning informal learning in contexts of natural resource management is non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…No one-not scientists, professionals, or lay peopleis immune to the consequences of this realization. Nonetheless, a complexity view of the world is rare (Sterman 1994, Morin 2008, and the majority of professionals, disciplinary scientists, and lay stakeholders/decision makers whom one-and certainly the authors-engages when conducting action research have yet to encounter complexity thinking/science. They display all the distinctly reductionist habits of expecting to come to "know" the problem and objectively find the "right" solution by dividing the problem into discrete elements to be tackled by experts who "know" how to do it (Zellmer et al 2006).…”
Section: The Challenge Of Shifting To a Complexity Frame Of Referencementioning
confidence: 99%